Middle Triassic SW Gondwana paleogeography and sedimentary dispersal revealed by integration of stratigraphy and U-Pb zircon analysis: The Santa Cruz Sequence, Paraná Basin, Brazil. (December 2018) - Philipp, Ruy P.; Schultz, Cesar L.; Kloss, Heiny P.; Horn, Bruno L.D.; Soares, Marina B.; Basei, Miguel A.S.
Abstract: The Paraná Basin represents an important sedimentation episode that occurred in the south margin of Gondwana during the Paleozoic and Mesozoic. The evolution of the basin extended mainly from the Ordovician to the Lower Cretaceous, with the continental break-up and the formation of the rift that originated the South Atlantic Ocean. The stratigraphy and depositional architecture of the Triassic strata in the southern portion of the basin are characterized by significant variations in depositional styles, interpreted as a response to tectonic and climatic changes. The sedimentary succession was grouped into three major chronostratigraphic intervals based on vertebrate ages (Late Permian-Early Triassic, Middle-Late Triassic and Early Cretaceous). The integration between stratigraphic and structural data with U-Pb ages of detrital zircon was used to investigate the origin and maximum depositional age of the Santa Maria Formation (Santa Cruz Sequence) which marks the Middle Triassic in the basin. This sequence is composed by conglomeratic sandstones with sandstones at the base, covered by a thick package of reddish mudstones containing vertebrate fossils. Paleocurrent data show N-NE sense of sedimentary transport, indicating that the sedimentation sources came from southwest Gondwana. The transition of the alluvial braidplain deposits of Sanga do Cabral Formation (Early Triassic) to the fluvial braided, floodplains and sinuous/anastomosing deposits, rich vertebrate fauna of the Santa Maria Formation (Middle-Late Triassic) indicates a sedimentation controlled by tectonic processes that uplifted the basement. The elongated positive feature of NW-SE strike named the Rio Grande Arch represented a topographic high and limited the deposition of the Triassic strata to south of the basin. The analyzed detrital zircon grains record the basement units located in southern Brazil and Uruguay. The main sources are the Tonian to Ediacaran rocks of the Dom Feliciano Belt and the sedimentary layers of the Paraná Basin deposited between the Carboniferous and the Permian that occur in the Sul-rio-grandense Shield, the source of the Paleozoic and Mesozoic age zircons. Archean to Mesoproterozoic ages are subordinate, between 2.7 and 2.0 Ga and 1.5–1.0 Ga. The siltstones of the upper portion of the sequence show elongated prismatic and euhedral zircon, aged 237 ± 1.5 Ma, defining the maximum deposition to the top of the Santa Cruz Sequence. These crystals zircon were deposited from ashes, probably originated from volcanic rocks of central and southern Argentina and associated with an extensional environment after the magmatism of the Choiyoi Province. Graphical abstract: Image 1 Highlights: Triassic sedimentation controlled by tectonic processes. U-Pb detrital zircon data show provenance of the Sul-rio-grandense Shield rocks area. Permian zircon grains are associated to reworking of Paraná Basin rocks (Rio Bonito and Irati formations). The ash fall zircons came from the Andean volcanism. 237 Ma is the maximum deposition age of Santa Cruz Sequence (Santa Maria Formation).